2003
DOI: 10.1002/bem.10169
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral and cognitive effects of microwave exposure

Abstract: This paper presents an overview of the recent behavioral literature concerning microwave exposure and discusses behavioral effects that have supported past exposure standards. Other effects, which are based on lower levels of exposure, are discussed as well, relative to setting exposure standards. The paper begins with a brief discussion of the ways in which behavioral end points are investigated in the laboratory, together with some of the methodological considerations pertinent to such studies when radio fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(32 citation statements)
references
References 92 publications
(114 reference statements)
1
30
0
Order By: Relevance
“…Because behavioral responses may be mobilized quickly and are of high gain, they must always be considered in any discussion of the thermoregulatory consequences of RF exposure. A separate white paper [D'Andrea et al, 2003] contains a summary of the behavioral responses that contribute to thermoregulation in the presence of RF fields.…”
Section: Thermoregulatory Behavior In the Presence Of Rf Energymentioning
confidence: 99%
“…Because behavioral responses may be mobilized quickly and are of high gain, they must always be considered in any discussion of the thermoregulatory consequences of RF exposure. A separate white paper [D'Andrea et al, 2003] contains a summary of the behavioral responses that contribute to thermoregulation in the presence of RF fields.…”
Section: Thermoregulatory Behavior In the Presence Of Rf Energymentioning
confidence: 99%
“…General concerns regarding the potential hazards of exposure to RF electromagnetic fields have led to many epidemiological investigations [Horn, 1995;Richter et al, 2000;Santini et al, 2000]. Several studies have suggested that exposure to RF electromagnetic fields can interact with behavior [D'Andrea et al, 2003;Heynick et al, 2003]. In vitro studies have reported the effects of RF radiation on several endpoints, including effects on DNA damage [Lai and Singh, 1995], chromosome aberrations [Vijayalaxmi et al, 2001], mutation [Gos et al, 2000], cell transformation , and gene expression [Kwee et al, 2001].…”
Section: Introductionmentioning
confidence: 99%
“…The ability of magnetic fields to alter mood has been established in experiments where patients have been exposed to strong magnetic fields using transcranial magnetic stimulation (TMS) [Fitzgerald et al, 2003] and magnetic resonance imaging (MRI) [Rohan et al, 2004]. Behavioural and cognitive effects have been well documented when electromagnetic exposure is of sufficient intensity to heat tissue [D'Andrea et al, 2003]. Low intensity electromagnetic fields, such as those in geomagnetic storms, do not have sufficient energy to heat tissue and their impact on human mood and behaviour is poorly understood.…”
Section: Introductionmentioning
confidence: 99%